Desertification increased in Argentinian Patagonia: anthropogenic interferences - Beier, Elissandro Voigt; Fernandes, Felippe; Poleto, Cristiano (Acta Scientiarum. Human and Social Sciences, 2016)
The United Nations [UN] declared 2015 as the International Year of Soils and hopes that this initiative will serve to mobilize society for the importance of soil as a key part of the environment and the dangers surrounding their degradation in the world. The work will address the desertification process in Argentinian Patagonia, in order to intensify this process over time by human occupation. For this analysis, we used historical and current references, addressing an evolutionary outlook, illustrated with maps and quantitative data. The methodology focused on analysis of the first records of the phenomenon, identification and perception of it as a problem that has natural characteristics, but this is powered by anthropic processes with a soil occupation which is different from what the environment would bear with exploration of possibilities that did not consider the native vegetation and the natural system. The results identified point to a sheep and cattle herd growth in parallel with the evolution of desertification. It is possible to mention the characters responsible for such changes, which result in an environmental, social and economic imbalance, and alternatives for the process to be attenuated or mitigated are suggested.